Resilience of auxiliary nurses providing nursing care to patients with intellectual disabilities at a public mental healthcare institution - Steven D.M. Nthekang; Emmerentia du Plessis (AOSIS, 2019)
Background: Although mental health is regarded by the International Council of Nurses as a very important element of wellness, healthcare to patients with intellectual disabilities still remains neglected and under-resourced in most societies. Auxiliary nurses are crucial in providing nursing care to patients with intellectual disabilities. These nurses may not be prepared to handle challenges in providing nursing care to these patients, but their resilience can help them to manage these challenges. Limited research is available with regard to the resilience of auxiliary nurses providing nursing care to patients with intellectual disabilities. Objectives: To explore and describe the perceptions of auxiliary nurses providing nursing care to patients with intellectual disabilities on their resilience and protective mechanisms and vulnerability factors that influence their resilience when providing nursing care to these patients. Method: A qualitative, descriptive inquiry approach was used. The population comprised approximately 220 auxiliary nurses providing nursing care to patients with intellectual disabilities at a mental healthcare institution. Auxiliary nurses were selected through purposive sampling with the assistance of a mediator. The sample size was determined by data saturation. The data were collected through four focus group interviews with altogether 32 participants. Results: Five main themes emerged from the data. Practical wisdom was applied by the participants. They also made use of different forms of interactions, including the application of strategies such as utilising induction programmes and being willing to learn, in order to remain resilient. Protective mechanisms and vulnerability factors influence their resilience. Conclusions: Recommendations to strengthen the resilience of auxiliary nurses caring for patients with intellectual disabilities were formulated from the research findings, including recommendations for nursing practice, education and nursing research. Informal peer support, as well as addressing ethical issues, improving nurse-patient communication, training to handle adverse working conditions, and continuing education and further research on the practical wisdom of auxiliary nurses, is recommended.